READINESS TO CHANGE IN JEMURSARI ISLAMIC HOSPITAL IN CHANGE TO BE A EDUCATIONAL HOSPITAL - Rina Dwi Novita; Nyoman Anita Damayanti (The Indonesian Journal of Public Health, 2020)
ABSTRACTSurabaya Islamic Hospital Foundation is preparing Jemursari Islamic Hospital to become an educational hospital bacause University of Nahdlatul Ulama Surabaya as a medical institution is required to have at least one primary educational hospital. Jemursari Islamic Hospital  has conducted self assessment related to the readiness to become educational hospital in 2017 and resulted in a total value of 88.34%. This research aims to describe the readiness to change at the Islamic Hospital Jemursari in the change into an educational hospital. This research was conducted at Islamic Hospital of Jemursari in period of October 2017-July 2018. This research is descriptive research because it describes readiness to change at Jemursari Islamic Hospital in the change to become educational hospital without any statistical calculation. This research is a quantitative research using cross-sectional method. Sampling method with proportional random sampling technique to get sample of 88 people spread in all work units at Jemursari Islamic Hospital. Data collection using questionnaires readiness guide for readiness assessment consisting of five indicators namely communication, sponsorship, stakeholder, readiness, and training. The results showed that the indicator of communication at Jemusari Islamic Hospital has the lowest average value (4.32) and has a slightly ready level. The stakeholder indicator has the highest average score (5.06) and has a ready level. In addition, indicators of sponsorship, readiness, and training have a ready level. In conclusion, based on these five indicators, most respondents (87,23%) at Jemursari Islamic Hospital are ready to change from non-educational hospital to educational hospital. The advice given is to improve communication related to the change into an educational hospital, so that all indicators become ready. Keywords: hospital, educational hospital, readiness to change